Decision Support System for The Program Indonesia Pintar Scholarship Using Simple Additive Weighting Method - Septiana, Yosep; Nuraeni, Fitri; Anisa, Kamelia (Politeknik Ganesha Medan, 2022)
The Program Indonesia Pintar (PIP) is an educational scholarship from the government for students who lack funds to continue their education, one of which is at the junior high school level. It is still done manually when selecting students who are eligible to receive the PIP scholarship at the junior high school level. This is less efficient because the selection process will take a long to analyze, and the reporting process is not yet computerized. To overcome these problems, a decision support system is needed to assist schools in selecting students who receive PIP assistance. The method used for the development of a decision support system is Simple Additive Weighting (SAW). The choice of this method is because the decision-making process is carried out by searching for the highest alternative from all alternatives so that the assessment is more accurate based on the provisions of the criteria values and preference weights. With the construction of this system, it is expected to be able to provide a solution so that the student selection decision-making process can be carried out quickly and accurately.